Elevated expression of the RAGE variant-V in SCLC mitigates the effect of chemotherapeutic drugs - Madhavan, Bindhu K.; Han, Zhe; Singh, Bishal; Bordt, Nico; Kaymak, Serap; Bandapalli, Obul Reddy; Kihm, Lars Philipp; Shahzad Hussain, Khurrum; Isermann, Berend; Herzig, Stephan; Nawroth, Peter Paul; Kumar, Varun (Cancers, 2021)
Small cell lung carcinoma (SCLC) is a highly aggressive malignancy with a very high mortality rate. A prominent part of this is because these carcinomas are refractory to chemotherapies, such as etoposide or cisplatin, making effective treatment almost impossible. Here, we report that elevated expression of the RAGE variant-V in SCLC promotes homology-directed DNA DSBs repair when challenged with anti-cancer drugs. This variant exclusively localizes to the nucleus, interacts with members of the double-strand break (DSB) repair machinery and thus promotes the recruitment of DSBs repair factors at the site of damage. Increased expression of this variant thus, promotes timely DNA repair. Congruently, the tumor cells expressing high levels of variant-V can tolerate chemotherapeutic drug treatment better than the RAGE depleted cells. Our findings reveal a yet undisclosed role of the RAGE variant-V in the homology-directed DNA repair. This variant thus can be a potential target to be considered for future therapeutic approaches in advanced SSLC.